Vascular Aging Is Accelerated in Flight Attendants With Occupational Secondhand Smoke Exposure. Issue 3 (March 2019) - Wei, Janet; Shufelt, Chrisandra; Oestreicher Stock, Eveline; Mills, Claire; Dhawan, Shivani; Jacob, Riya; Torbati, Tina; Cook-Wiens, Galen; Benowitz, Neal; Jacob, Peyton; Ganz, Peter; Bairey Merz, Cathleen Noel; et al.
Abstract : Objective: To determine whether early vascular aging may be present in flight attendants with remote in-cabin secondhand smoke (SHS) exposure. Methods: Twenty-six flight attendants with a history of in-cabin SHS exposure prior to the airline smoking bans were recruited. Pulse wave analysis, peripheral arterial tonometry, and brachial artery reactivity testing evaluated their arterial compliance and endothelial function. Results: Flight attendants with remote in-cabin SHS exposure have normal blood pressure, pulse wave velocity, and reactive hyperemia index, but abnormal pulse pressure, augmentation index, flow-mediated dilation, and hyperemic mean flow ratio. Conclusion: These preliminary findings suggest that flight attendants with remote in-cabin SHS exposure have preclinical signs of accelerated vascular aging and raise new questions about the relationship between remote SHS exposure and vascular health.